PERAN PESANTREN MODEREN DALAM PENGEMBANGAN KARAKTER DAN PENDIDIKAN INKLUSIF - Ahmad Farid; Alya Fatunnisa; Jeslin Simson Stiawan; Lifiyanti Lifiyanti; Jumanah, Jumanah; Shinta Juliana Putri; Siti Nurlina (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Modern Islamic boarding schools have an important role in Islamic education in Indonesia, especially in character formation and implementing inclusive education. This research aims to analyze the role that exists in modern Islamic boarding schools, as well as the challenges and strategies implemented. This research method uses qualitative methods by managing Islamic boarding schools in the interests of inclusive education. In the context of inclusive education, modern Islamic boarding schools develop inclusive learning methods. This research concludes that modern Islamic boarding schools have great potential in character building by providing inclusive education